Pengaruh Dukungan Organisasi, Lingkungan Kerja dan Komunikasi terhadap Kinerja Pegawai pada Dinas Penanaman Modal dan Pelayanan Terdapadu Satu Pintu Muaro Jambi - Gilang Romadon; Sumarni Sumarni; Rohman Wilian (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to determine the effect of organizational support, work environment, and communication on employee performance at the Investment and One-Stop Integrated Services Office (DPM-PTSP) of Muaro Jambi Regency, both partially and simultaneously. The method used is quantitative analysis with a population and sample consisting of all 44 employees, determined through a saturated sampling technique. Data were collected using a Likert scale-based questionnaire, and the analysis was carried out using multiple linear regression with the help of SPSS software. The results of the study showed that (1) organizational support has a positive and significant effect on employee performance, (2) work environment has a positive and significant effect on employee performance, (3) communication has a positive and significant effect on employee performance, and (4) organizational support, work environment, and communication simultaneously have a positive and significant effect on employee performance. The recommendations/suggestions from this research are expected to improve employee performance by enhancing organizational support through fair task distribution, reward programs, and development opportunities; creating a comfortable and well- equipped work environment that encourages productivity; and strengthening effective communication between superiors and subordinates as well as among employees through regular meetings and discussion forums.